Formulation and Nutrient Component Analysis of Various Cost-Effective Bacterial Culture Media Based on Horticultural Waste - Handarini; Putri Sopiyani; Deni Farizal; Alby Salman Al Farizi MK; Wasiyah Khusna Fadhilah (Jurnal Penelitian Pendidikan IPA, 2025)
Horticultural waste, which is often overlooked, has great potential as an alternative raw material for cost-effective and environmentally friendly culture media. This study aims to develop a cost-effective alternative bacterial culture media formulation by utilizing horticultural waste. In addition, this study also aims to analyze the nutritional components of the formulated media to ensure its effectiveness in supporting bacterial growth. The results showed that E. coli was able to grow on all types of test media. This indicates slower growth compared to the control media. The average number of E. coli colonies on BW Agar and CW Agar at concentrations of 10%, 15%, and 20% after incubation for 48 hours was >300 CFU/mL. Meanwhile, the average number of E. coli colonies on PW Agar at concentrations of 10%, 15%, and 20% was 126 × 10⁷ CFU/mL, 171 × 10⁷ CFU/mL, and 225 × 10⁷ CFU/mL, respectively. The number of S. aureus colonies was only obtained on BW Agar with concentrations of 10%, 15%, and 20%, namely 77 × 10⁷ CFU/mL on BW Agar 10%, 200 × 10⁷ CFU/mL on BW Agar 15%, and 300 × 10⁷ CFU/mL on BW Agar 20%. Based on these results, the optimal formulations representing each type of test media selected for nutrient content analysis were BW Agar 20%, CW Agar 20%, and PW Agar 20%.